Feminist Considerations in Research Recruitment for Pregnant Persons in Justice-Involved Contexts. - Carpenter, Hannah; McNamara, Victoria H.; Yu, Xiang; Campo-Engelstein, Lisa; Smith, Elise M. (American Journal of Bioethics, 2026)
The article focuses on ethical and regulatory considerations in recruiting justice-involved pregnant individuals with opioid use disorder (OUD) for the Healthy Brain and Child Development Study (HBCD). It recommends applying the provisions of 45 CFR 46 Subpart C, which governs research involving prisoners, due to the overlap between OUD and justice involvement, to preempt regulatory complications if participants become incarcerated during the study. Using a feminist ethics framework, the article advises including data on biological fathers, ensuring Institutional Review Board (IRB) representation with relevant lived experience, minimizing legal risks heightened by recent changes in reproductive rights law, and addressing historical exclusion of pregnant and incarcerated populations from research to promote equitable inclusion and protect participant autonomy.